An investigation on the level of dental senior students knowledge about endocarditis prophylaxis incases with cardiac disease receiving dental treatment - Fakhraee AH; Eslami M; Hosseini Kakroodi AR (Tehran University of Medical Sciences, 2004)
Dental practices such as oral, periodontal and endodontic surgeries cause damages to"nthe intraoral tissues, so having knowledge of the dental procedures that necessiciate endocarditis prophylaxis"nis of high importance."nPurpose: The aim of the present study was to determine the knowledge level of dental senior students in"nTehran dental faculties about endocarditis,"nMaterials and Methods: In this cross- sectional descriptive- analytic study, 253 senior students of four"ndentistry faculties in Tehran took part as follows: Tehran University: 71 students (M:42, F:29), Shahid"nBeheshti University: 74 students (M:40, F:34), Shahed University: 35 students (M:35, F:38), Azad University:"n73 students (M:35, F:38). The questionnaire used in this research consisted of three parts as follows: part one:"ninformation on cardiac diseases, part two: dental procedures requiring endocarditis prophylaxis, part three:"nantibiotic diet in endocarditis prophylaxis. Sex and place of education of the students were also studied in"ndetail. For statistical analysis, Chi-square test was used."nResults: On the basis of the sex, the correct answers of the female respondents of different universities were"nranked as: Azad University: 72.5%, Tehran University: 71.1%, Shahid Beheshti: 57%, ShahedUniversity:"n55.7%. In the same way, the male respondents were reported as: Tehran Universitys: 71.6%, Azad University:"n66.2%, Shahed University: 57.3%, Shahid Behesti University: 52.1%, On the basis of the place of education,"nthe following results were reported: Tehran University students managed to answer 71.3% , Azad University,"nShahed University and Shahid Beheshti University students could answer 69.5%, 56.5% and 54.6%,"nrespectively. All these differences were statistically significant, indicating that first ranked students have more"ninformation than the students of other schools."nConclusion: It is recommended to develop more practical training programme in dental schools on cardiac"ndiseases, dental procedures requiring endocarditis prophylaxis and antibiotic diets.